'Is it the crime of the century?'. (July 2015) - MacDonald, Joanna; Garvie, Christopher; Gordon, Sarah; Huthwaite, Mark; Mathieson, Fiona; Wood, Amber-Jane; Romans, Sarah
<x xml:space="preserve">Abstract</x> Given the longstanding controversy about hypnosedative use, we aimed to investigate the attitudes of prescribing psychiatrists and service users towards long-term use of hypnosedative medication, and their perceptions of barriers to evidence-based nonmedication alternatives. Qualitative data from focus groups in Aotearoa/NZ were analysed thematically. A novel research design involved a service user researcher contributing throughout the research design and process. Service users and psychiatrists met to discuss each other's views, initially separately, and subsequently together. Analysis of the data identified four key themes: the challenge, for both parties, of sleep disturbance among service users with mental health problems; the conceptual and ethical conflicts for service users and psychiatrists in managing this challenge; the significant barriers to service users accessing evidence-based nonmedication alternatives; and the initial sense of disempowerment, shared by both service users and psychiatrists, which was transformed during the research process. Our results raise questions about the relevance of the existing guidelines for this group of service users, highlight the resource and time pressures that discourage participants from embarking on withdrawal regimes and education programmes on alternatives, highlight the lack of knowledge about alternatives and reflect the complex interaction between sleep and mental health problems, which poses a significant dilemma for service users and psychiatrists.